O processo civilizacional da tourada Guerreiros, cortesãos, profissionais... e bárbaros? - Ampudia de Haro, Fernando (Imprensa de História Contemporânea, 2020)
This book challenges conventional wisdom about bullfighting. With an innovative approach, based on the work of Norbert Elias, the author argues bullfight is the result of the interaction between transformations of society and decisions that aim to create bullfighting rules. In the course of history, bullfighting became civilized, that is, pacified, in the sense that the level of self-control in the conduct and emotions of both bullfighters and public increased. This does not mean that violence has disappeared, but that it has acquired new traits. This historical path, from the 15th century to the present, is reconstructed in these pages by analyzing bullfighting in Portugal through the viewpoint of the regulation of violence, its public exposure and its relationship with the population's patterns of behavior and sensitivity.